![image](https://tex.z-dn.net/?f=+lim+%5C+x-%3E+5+%5C+%5C+%5C+%5Cfrac%7Bx%5E2-11x%2B30%7D%7Bx%5E2-25%7D%5C%5C%0A+lim+%5C+x-%3E+5+%5C+%5C+%5C+%5Cfrac%7Bx%5E2-11x%2B30%7D%7Bx%5E2-25%7D%5C%5C%0A+lim+%5C+x-%3E+5+%5C+%5C+%5C+%5Cfrac%7B%28x-6%29%28x-5%29%7D%7B%28x-5%29%28x%2B5%29%7D%5C%5C%0A+lim+%5C+x-%3E+5+%5C+%5C+%5C+%5Cfrac%7Bx-6%7D%7Bx%2B5%7D+%3D+-%5Cfrac%7B1%7D%7B10%7D)
5 \ \ \ \frac{x^2-11x+30}{x^2-25}\\
lim \ x-> 5 \ \ \ \frac{x^2-11x+30}{x^2-25}\\
lim \ x-> 5 \ \ \ \frac{(x-6)(x-5)}{(x-5)(x+5)}\\
lim \ x-> 5 \ \ \ \frac{x-6}{x+5} = -\frac{1}{10}" alt=" lim \ x-> 5 \ \ \ \frac{x^2-11x+30}{x^2-25}\\
lim \ x-> 5 \ \ \ \frac{x^2-11x+30}{x^2-25}\\
lim \ x-> 5 \ \ \ \frac{(x-6)(x-5)}{(x-5)(x+5)}\\
lim \ x-> 5 \ \ \ \frac{x-6}{x+5} = -\frac{1}{10}" align="absmiddle" class="latex-formula">